Development of critical and transformative pedagogy in current university education - Moya Rojas, Nicanor (2019)
This article is about the necessary foundations to promote the critical and transforming pedagogy, which was under the responsability of the university professors, whom have the high mission of educating to the future professionals for the progress of the country; promoting the knowledge and social, economic and educational change, in the perspective of achieving a humanist, right and democratic society, and at the same time, to lead the actual economic model, which is neoliberal and educational, and it limits the national development. For all those reasons,  it is important to practice the critical and thoughtful attitude of the philosophy and the scientific pedagogy.